Race and satisfaction in general OB/GYN clinics - Rohrer James E; Lund Jon D; Goldfarb Susan (BMC, 2005)
Abstract Background The purpose of this study was to test the hypothesis that racial differences in satisfaction can be found among OB/GYN patients on a US naval base. Methods Cross-sectional surveys assessing satisfaction with services were obtained from 838 patients who were seen in one of the two general OB/GYN clinics (455 in the base hospital clinic and 391 in a satellite clinic). Multiple logistic regression analysis was used to identify subgroups of patients who were not very satisfied with care received. Results When the patients seen in the base hospital were analyzed separately, Asian respondents had significantly lower odds of being very satisfied relative to non-Hispanic white respondents (AOR = .33, p < .01). Conclusion Asian patients may be less satisfied than others when treated at a larger facility. Patients treated at a satellite clinic tended to be more satisfied than patients seen at the base hospital.